Investigation of the Effect of Silica and Phosphorus Content on the Performance of Active Matrix as Component of Cracking Catalyst - Gunawan, Melia Laniwati; Rasrendra, Carolus Borromeus; Widikrama, Candra Lutfi; Kurniawan, Rizky Gilang; Nisa, Lita Marina; Hudaya, Farhansyah Yusuf Putra; Makertihartha, I G. B. N.; Subagjo, Subagjo (Journal of Engineering and Technological Sciences, 2024)
Fluid catalytic cracking (FCC) is a technique that converts heavy-fraction feed into fuel. The FCC catalyst components consist of a composite material made of zeolite, filler, binder, and an active matrix. The active matrix is used as a pre-cracker for the heavy-fraction feed. This study examined the impact of the Si/Al ratio and the addition of phosphorus on the physical properties and activity of the active matrix. The synthesis technique refers to US patent 6723297 B2. The utilized variants consisted of SiO2 ranging from 50 to 80 weight percent and a phosphorous addition ranging from 1 to 2 weight percent. The physical characteristics of the active matrix were assessed using nitrogen physisorption and NH3-Temperature programmed adsorption/desorption techniques. A chemical activity test was conducted using the micro activity test (MAT) method, with vacuum gas oil (VGO) as the feedstock. This test was done in accordance with the ASTM D 5154 – 03 standard. The results indicated that the silica composition in the active matrix is directly related to the average pore diameter but inversely related to the specific surface area. Additionally, the inclusion of phosphorus had a similar impact. The silica-alumina-phosphorous variant containing 75%-wt of SiO2 exhibited the most superior active matrix activity, achieving the maximum acquisition of light cycle oil (LCO) at 33%-wt.